2014
DOI: 10.5694/mja13.00112
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the expansion of the National Bowel Cancer Screening Program

Abstract: Objective(s) To estimate the impact of various expansion scenarios of the National Bowel Cancer Screening program (NBSCP) on the number of bowel cancer deaths prevented. Impact of the expansion scenarios on colonoscopy demand was also investigated. Design MISCAN-Colon, a well-established, validated computer simulation model for bowel cancer screening, was adjusted to reflect the Australian situation. In July 2013, we simulated the effects of screening over a 50 year period, starting in 2006. The model parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
2
24
1
Order By: Relevance
“…We suggest that capsule colonoscopy (if available) is an appropriate screening test when patients decline colonoscopy, FIT, FIT-fecal DNA, CT colonography, and fl exible sigmoidoscopy (weak recommendation, low-quality evidence). 6 . We suggest against Septin9 for CRC screening (weak recommendation, low-quality evidence).…”
mentioning
confidence: 99%
“…We suggest that capsule colonoscopy (if available) is an appropriate screening test when patients decline colonoscopy, FIT, FIT-fecal DNA, CT colonography, and fl exible sigmoidoscopy (weak recommendation, low-quality evidence). 6 . We suggest against Septin9 for CRC screening (weak recommendation, low-quality evidence).…”
mentioning
confidence: 99%
“…Since 2008, the United States Preventive Services Task Force no longer recommends routine CRC screening in regularly screened individuals aged 75 years or older based on two CRC screening models suggesting that the benefit of continued screening in this age group is very small compared to the additional burden [16]. In 2014, the Australian government accelerated the expansion of their national CRC screening program when modeling indicated that this acceleration would increase the number of additional deaths prevented by the program by 35% [17]. Just recently in 2014, the Netherlands changed the cut-off used to define a positive FIT in their national CRC screening M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 12 program because following launch of the program many more individuals required colonoscopy for diagnostic follow-up than could be offered with the available colonoscopy capacity.…”
Section: A N U S C R I P Tmentioning
confidence: 96%
“…Its findings are broadly consistent with recent modeling that, even on modest participation rates, the NBCSP would prevent 70 000 premature Australian deaths over the next 3-4 decades. 4 Another special feature of the study is the way linkage has been used to identify cancers in those with negative screening tests. Of the 1063 cases of cancer in the 2006-2008 participants, 887 (83.4%) were detected following a positive screening test.…”
Section: Key Findingsmentioning
confidence: 99%
“…[2][3][4] Having been involved in the NBCSP's development and promotion over many years (from a non-government perspective), we take this opportunity to comment on the study and to add context in relation to program developments since 2011. In our view, it provides evidence of benefit worthy of consideration across the Asia-Pacific region.…”
mentioning
confidence: 99%